ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PEDAGANG DI PASAR TRADISIONAL CINERE DEPOK - puji yuniarti (Widya Cipta - Jurnal Sekretari dan Manajemen, 2019)
This study studied what factors influence the income of traders in the Cinere Tradisional Market Depok. This study uses descriptive quantitative research with a total of 50 traders. The sample in this study amounted to 50 respondents taken through the Proportionate Stratified Random Sampling technique. While the data collection method uses questionnaires and interviews. The variables used include education level (X1), Business Capital (X2), Costs (X3), Duration of Business (X4) Working Hours (X5) and merchant income (Y). Data analysis used is multiple linear regression model of ordinary least square (OLS) with a significance level of 5%. The results of the study showed that the variable partial variables that significantly affect the merchant income of traders Cinere traditional  market includes business capital (X2), Costs (X3) and working hours (X4). While the level of education variable (X1) and duration of business (X4) is not suitable for the income of traders in the Cinere traditional market Depok. Furthermore, the variables of business capital, costs,  and working hour together have a significant effect on the income of traders in the Cinere Traditional market Depok. The influence of dependent variables similarly gave significant influence towards the merchant income was in the percentage of 56,1% and the remaining 43,9% is affected by the other variables.